Florence Nightingale : the courageous life of the legendary nurse - Reef, Catherine (Boston : Clarion Books, Houghton Mifflin Harcourt, 2017)
"A biography for young adult readers on Florence Nightingale, the pioneering nurse best known for her work during the Crimean War, where she rectified horrifying conditions and made nightly rounds to check on patients, saving hundreds of lives and sparking worldwide healthcare reform"--
The night gallery -- "Mistress of all she attempts" -- A woman with work to do -- "Dust and nothing" -- The prison called family -- Shadows in a thirsty land -- "But one person in england" -- The horrors -- An angel with a lamp -- Nightingale power -- Maid of all work -- A noble life.
Includes bibliographical references (pages 174-176) and index.
Ages 12+.
Keywords: Nightingale, Florence, -- 1820-1910 -- Juvenile literature; Nurses -- England -- Biography -- Juvenile literature